(3QjGV GdfahS aj WHbGJ abgGA eOjfI GdbjQhGfs - (3CHh HcQ YHO Gddg Hf eMeO Hf YHO Gddg GdeGdcj, GdeGdcj,J (B453 (3g` s ((3jhSa Hf eMeO Hf YHOGdhgGH Hf jhSa GdeGdcj s)
(3ChdgG (B:s
(3jHJOF ef PcQ haGI CHj YbGd GHf YdhGf GdPi Jhaj SfI (B293 s
(3BNQgG (B:s
(3QhGjI Yf CHj HcQ Hf YHOGdQMef Gdabjg s
(3oeQJH Ydi GdSfjf GdgLQjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B121s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B138 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B77 s
Keywords: (3GdJGQjNs